Complete mitochondrial genome of the Japanese pine sawyer, Monochamus alternatus (Coleoptera: Cerambycidae). (3rd March 2016) - Li, Fengbo; Zhang, Huixian; Wang, Wei; Weng, Hongbiao; Meng, Zhiqi
Abstract: We determined the complete mitochondrial genome of the Japanese pine sawyer Monochamus alternatus Hope (Coleoptera: Cerambycidae), which is a major forest pest in Asia. The genome is 15, 874 bp in length containing 37 typical animal mitochondrial genes and one non-coding A+T-rich region. Its gene content and order are typical of other coleopteran mitochondrial genomes described to date. All protein-coding genes (PCGs) are initiated by ATN codons. Eight PCGs use complete stop codons TAG or TAA, whereas other PCGs end with a single T. All tRNA genes show typical secondary cloverleaf structures except for tRNA Ser(AGN), which lacks the dihydrouridine (DHU) arm. The large non-coding A+T-rich region of 1249 bp contains a 14 bp-long poly-T stretch and two microsatellite-like (AT)(TA)7 and (TA)8 elements.